Peran Adaptive Leadership Presiden Indonesia Dalam Penanganan Covid-19 Rawan Korupsi - Amalia Syauket (Jurnal Kajian Ilmiah, 2021)
Abstract The Covid-19 Handling Drama is a national leadership test event. On the other hand, society will depend on its leader and as a leader, he must meet the high expectations of himself. The Covid-19 pandemic is a threat in itself for the Government of Indonesia, if it cannot balance between encouraging economic activity (political interests) and public health (an urgent situation). This article explores the phenomenon of the central role of adaptive leadership in dealing with the Covid-19 pandemic based on constitutional rights taken to save people's lives, but the potential for corruption by using the Normative Juridical approach that prioritizes secondary data. The conclusion that can be drawn from this article is that there is no single best cure for winning this battle because the "opponent" of the current government is a growing virus. In handling the covid-19 virus pandemic, an adaptive leader is needed, namely a Leader who has authority as a consequence of the President's authority as head of state and head of government. President Joko Widodo uses his constitutional right to issue Government Regulation in Lieu of Law (Perpu) number 1 year 2020 concerning State Financial Policy and Financial System Stability for Handling the 2019 Corona Virus Disease (COVID-19) Pandemic and / or in the Context of Facing Threats that Endanger the National Economy and / or Financial System Stability. Adaptive Leadership is a form of Adaptive Governance in Handling Covid-19 but is prone to corruption. Keywords: Adaptive Leadership and the Constitutional Rights of the President of the Republic of Indonesia, Prone to Corruption Abstrak Drama Penanganan Covid-19 adalah ajang uji kepemimpinan Nasional. Disisi lain, masyarakat akan sangat tergantung pada pemimpinnya dan sebagai seorang pemimpin, dia harus memenuhi tingginya ekspektasi terhadap dirinya. Pandemi Covid-19 merupakan ancaman tersendiri bagi Pemerintah Indonesia, bila tidak dapat menyeimbangkan antara mendorong aktivitas perekonomian (kepentingan politik) dan kesehatan public (keadaan mendesak). Artikel ini menelusuri fenomena peran sentral kepemimpinan adaptif dalam menangani pandemic covid-19 berdasarkan hak konstitusional yang diambil untuk menyelamatkan jiwa masyarakat, namun potensi korupsinya dengan menggunakan pendekatan Juridis Normatif yang mengutamakan data sekunder. Kesimpulan yang dapat ditarik dari artikel ini bahwa tidak ada satu obat yang paling mujarab untuk memenangkan pertempuran ini sebab ‘lawan’ pemerintah kali ini adalah virus yang terus berkembang. Dalam melakukan penanganan pandemic virus covid-19 dibutuhkan seorang pemimpin yang adaptif yaitu Leader yang mempunyai Otoritas sebagai konsekwensi dari kewenangan Presiden sebagai kepala Negara dan kepala pemerintahan .Presiden Joko Widodo menggunakan hak konstitusionalnya untuk menerbitkan Peraturan Pemerintah Pengganti Undang-undang (Perpu) nomor 1 tahun 2020 tentang Kebijakan Keuangan Negara dan Stabilitas Sistem Keuangan untuk Penanganan Pandemi Corona Virus Disease 2019 (COVID-19) dan/atau dalam Rangka Menghadapi Ancaman yang Membahayakan Perekonomian Nasional dan/atau Stabilitas Sistem Keuangan. Adaptive Leadership ini merupakan bentuk Adaptive Governance dalam Penanganan Covid-19 namun rawan terjadinya korupsi. Kata kunci: Adaptive Leadership dan Hak Konstitusional Presiden RI, Rawan Korupsi